2012
DOI: 10.1111/mmi.12102
|View full text |Cite
|
Sign up to set email alerts
|

Spo0A links de novo fatty acid synthesis to sporulation and biofilm development in Bacillus subtilis

Abstract: SummaryDuring sporulation in Bacillus subtilis, the committedcell undergoes substantial membrane rearrangements to generate two cells of different sizes and fates: the mother cell and the forespore. Here, we demonstrate that the master transcription factor Spo0A reactivates lipid synthesis during development. Maximal Spo0A-dependent lipid synthesis occurs during the key stages of asymmetric division and forespore engulfment. Spo0A reactivates the accDA operon that encodes the carboxylase component of the acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(115 citation statements)
references
References 93 publications
7
105
1
Order By: Relevance
“…Spo0A, a transcriptional regulator of spore formation in B. subtilis, has also been identified as a regulator of de novo fatty acid synthesis and was found to be required for biofilm formation. The inability of an Spo0A-deficient mutant to form biofilms in vitro was restored by exogenous fatty acid supplementation (69). Likewise, fatty acid kinase A has been shown to be an important determinant of biofilm formation in Staphylococcus aureus strain USA300 (70).…”
Section: Discussionmentioning
confidence: 83%
“…Spo0A, a transcriptional regulator of spore formation in B. subtilis, has also been identified as a regulator of de novo fatty acid synthesis and was found to be required for biofilm formation. The inability of an Spo0A-deficient mutant to form biofilms in vitro was restored by exogenous fatty acid supplementation (69). Likewise, fatty acid kinase A has been shown to be an important determinant of biofilm formation in Staphylococcus aureus strain USA300 (70).…”
Section: Discussionmentioning
confidence: 83%
“…In B. subtilis , the phospholipid composition remained relatively unchanged during exponential growth, but the amount of PG slightly decreased while the amount of PE slightly increased during stationary growth. It has also been shown that the phospholipid composition of the forespore membrane changes during early stages of sporulation in B. subtilis [14]. …”
Section: Formation Of Lipid Domainsmentioning
confidence: 99%
“…These sigma factors, subunits of RNA polymerase, recognize specific sets of promoter sequences and allow transcription of different genes. Recently, it was discovered that Spo0A reactivates de novo fatty acid and phospholipids synthesis for membrane biogenesis during transient genetic asymmetry and after asymmetric cell division [14]. These authors suggested that de novo lipid synthesis was asymmetrically excluded from the forespore (Figure 1D).…”
Section: Changes In Lipid Composition Of the Membranes During Spormentioning
confidence: 99%
“…Similar to Ref. 1, we focused on the cell wall, but in the ESI † we also considered the role of the membrane [14] (Figs. S1a-b in ESI †).…”
Section: General Equation For Cell-wall Dynamicsmentioning
confidence: 99%
“…The mother cell synthesizes considerable amounts of membrane, also required for compartment-specific expression of transcription factors [14,21]. To study the effect of membrane synthesis on the cell wall, we extended the minimal model in the ESI † to include the membrane surface areas (Fig.…”
Section: Minimal Model Of Engulfmentmentioning
confidence: 99%